Analisis Peraturan E-Commerce di Indonesia terhadap Ketentuan Trans Pacific Partnership - Bagus Wicaksena; Sri Milawati Asshagab (Jurnal Hukum, 2022)
President Joko Widodo stated that Indonesia intended to join the Trans Pacific Partnership (TPP). In international treaties, when a country becomes part of international cooperation, the country is obliged to adjust its national law. The TPP consists of 30 Chapters, where the regulation regarding e-commerce is specified in Chapter 14. If Indonesia becomes part of the TPP, then the domestic e-commerce regulations must be adjusted according to the provisions that apply to the TPP. By employing the normative legal research method, this analysis aims to analyze laws and regulations related to e-commerce in Indonesia and e-commerce provisions in the TPP and identify the gaps between them. The results of the analysis show that if Indonesia joins the TPP, the Indonesian government needs to make adjustments to several regulations, such as Law Number 11 of 2008 as amended by Law Number 19 of 2016; Law Number 7 of 2014) of Law Number 11 of 2020; Government Regulation Number 71 of 2019; and Government Regulation Number 80 of 2019.Â Presiden Joko Widodo menyatakan bahwa Indonesia bermaksud untuk bergabung dengan Trans Pacific Partnertship (TPP). Dalam perjanjian internasional, ketika suatu negara menjadi bagian dari suatu kerjasama internasional, maka negara tersebut wajib menyesuaikan hukum nasionalnya. TPP terdiri dari 30 Chapter, dimana pengaturan mengenai e-commerce terdapat pada Chapter 14. Apabila Indonesia menjadi bagian dari TPP, maka regulasi e-commerce di dalam negeri harus disesuaikan menurut ketentuan yang berlaku pada TPP. Dengan menggunakan metode analisis yuridis normatif, tulisan ini bermaksud untuk menelaah peraturan perundang-undangan mengenai e-commerce di Indonesia dan ketentuan e-commerce dalam TPP serta menganalisis kesenjangan di antara keduanya. Hasil analisis menunjukkan bahwa apabila Indonesia bergabung dengan TPP, maka pemerintah Indonesia perlu mengadakan penyesuaian terhadap beberapa peraturan dalam Undang-Undang Nomor 11 Tahun 2008 jo. Undang-Undang Nomor 19 Tahun 2016; Undang-Undang Nomor 11 Tahun 2020; Peraturan Pemerintah Nomor 71 Tahun 2019; dan Peraturan Pemerintah Nomor 80 Tahun 2019.